Analysis of Family Resilience: The Effects of the COVID-19 - Dony Darma Sagita; Mutiara Felicita Amsal; Shafna Utami Nur Fairuz (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2020)
This study aims to analyze family resilience during the COVID-19 pandemic. The COVID-19 pandemic is a worldwide health problem at this time, including Indonesia, with a massive spread. Various issues arise due to the COVID-19 pandemic in economic, social, cultural, educational, and social welfare. This research was conducted on the people who lived in the COVID-19 red zone at Jabodetabek (Jakarta, Bogor, Depok, Tangerang, and Bekasi) area, with a total sample of 311 people. This study's data are political data collected using the Family Resilience instrument distributed using the Google Form application and data analysis using the Rasch Model and SPSS. Based on the research, it was found that the level of family resilience during the COVID-19 pandemic was in a suitable category. Therefore, it is necessary to increase parents' understanding in maintaining harmony and stability in the family conditions.